Analysis of current testing practices for biallelic MUTYH mutations in MUTYH‐associated polyposis. (10th May 2014) - Landon, M.; Ceulemans, S.; Saraiya, D.S.; Strike, B.; Arnell, C.; Burbidge, L.A.; Moyes, K.; Theisen, A.; Fernandes, P.H.; Ji, J.Q.; Abbott, B.; Kaldate, R.R.; et al.
Abstract: MUTYH ‐associated polyposis (MAP) is an autosomal recessive syndrome caused by biallelic mutations in the base excision repair gene MUTYH . Owing to potential limitations in the MAP testing strategy and testing criteria, it is possible that MAP is being under‐identified both genotypically and phenotypically. To determine whether full sequencing of MUTYH would increase clinical sensitivity over a founder mutation (FM) strategy, a retrospective analysis of two datasets from a commercial clinical laboratory was performed. The first cohort contained 1522 individuals who received MUTYH analysis for two FMs with subsequent full‐gene sequencing. Eighty‐five biallelic individuals were identified; 47 carried two FMs, 17 carried one FM and one mutation identified on full sequencing, and 21 carried biallelic mutations identified only on full sequencing. The second cohort contained 921 patients with colorectal cancer <50 years and <10 reported colorectal adenomas who had undergone MUTYH mutation testing. In this cohort, 19 of 921 (2.1%) individuals were identified as biallelic MUTYH carriers. Of these, 13 did not have a personal or family history of polyps and would not have met guidelines for MUTYH testing. These results suggest that individuals with biallelic MUTYH mutations are under‐ascertained based on both genotype and phenotype under current standard testing practices.